Transcriptome profiling revealed novel transcriptional regulators in maize responses to Ostrinia furnacalis and jasmonic acid. - Hai Wang; Shengyan Li; Shouzhen Teng; Haisheng Liang; Hongjia Xin; Hongjiang Gao; Dafang Huang; Zhihong Lang (PLoS ONE, 2017)
Chewing insects cause severe yield losses in crop production worldwide. Crop plants counteract chewing insects by transcriptionally promoting a repertoire of defense gene products that are either toxic to, or attractive to the natural enemies of, pest insects. However, the complexity of the transcriptional reprogramming in plant defense response against chewing insects is still not well understood. In this study, the genome-wide early responses in maize seedlings to Asian corn borer (ACB, Ostrinia furnacalis) and also to jasmonic acid(JA), the pivotal phytohormone controlling plant defense response against herbivory, were transcriptionally profiled by RNA-Seq. Clustering of differentially expressed genes (DEGs) along with functional enrichment analysis revealed important biological processes regulated in response to ACB infestation and/or jasmonic acid. Moreover, DEGs with distinct expression patterns were differentially enriched with diverse families of cis-elements on their promoters. Multiple inventories of differentially expressed transcription factors (DETFs) in each DEG group were also analyzed. A transient expression assay using transfected maize protoplastswas established to examine the potential roles of DETFs in maize defense response and JA signaling, and this was used to show that ZmNAC60, an ACB- and JA-inducible DETF, represented a novel positive regulator of JA and defense pathway genes. This study provided a comprehensive transcriptional picture for the early dynamics of maize defense responses and JA signaling, and the identification of DETFs offered potential targets for further functional genomics investigation of master regulators in maize defense responses against herbivory.